Improving Walking Economy With an Ankle Exoskeleton Prior to Human-in-the-Loop Optimization - Wang, Wei; Chen, Jianyu; Ding, Jianquan; Zhang, Juanjuan; Liu, Jingtai (Frontiers in Neurorobotics, 2022)
Lower limb robotic exoskeletons have shown the capability to enhance human locomotion for healthy individuals or to assist motion rehabilitation and daily activities for patients. Recent advances in human-in-the-loop optimization that allowed for assistance customization have demonstrated great potential for performance improvement of exoskeletons. In the optimization process, subjects need to experience multiple types of assistance patterns thus leading to a long evaluation time. Besides, some patterns may be uncomfortable for the wearers thereby resulting in unpleasant optimization experiences and inaccurate outcomes. In this paper, we investigated the effectiveness of a series of ankle exoskeleton assistance patterns on improving walking economy prior to optimization. We conducted experiments to systematically evaluate the wearers’ biomechanical and physiological responses to different assistance patterns on a lightweight cable-driven ankle exoskeleton during walking. We designed nine patterns in the optimization parameters range which varied peak torque magnitude and peak torque timing independently. Results showed that metabolic cost of walking was reduced by 17.1 ± 7.6% under one assistance pattern. Meanwhile, soleus muscle activity was reduced by 40.9 ± 19.8% with that pattern. Exoskeleton assistance changed maximum ankle dorsiflexion and plantarflexion angle and reduced biological ankle moment. Assistance pattern with 48% peak torque timing and 0.75 N · m · kg−1 peak torque magnitude was effective in improving walking economy and can be selected as an initial pattern in the optimization procedure. Our results provided a preliminary understanding about how human respond to different assistances and can be used to guide the initial assistance pattern selection in the optimization.